Preparation method and application of a highly efficient electron transport MOF-based porous liquid photocatalyst
By introducing amide bonds into the MOF-based porous liquid photocatalyst, the problem of aggregation and instability of MOF nanoparticles in the liquid phase is solved, the CO2 reduction efficiency and stability are significantly improved, and the efficient photocatalytic reduction effect is achieved.
Patent Information
- Application Number
- CN202211639976.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-20
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2042-12-20
AI Technical Summary
The existing photocatalytic CO2 reduction reactions have MOF nanoparticles aggregation and instability in the liquid phase, which limits its efficiency and stability.
By introducing NH2-UIO-66 as a carrier, the surface is loaded with a large amount of CdS and combined with the [M2070][IPA] ionic liquid of macromolecular size to form amide bonds, improving the dispersion of MOF-based porous liquid and electron transport efficiency.
The CO2 reduction efficiency and stability of the MOF-based porous liquid photocatalyst was significantly improved, and the CO yield reached 71.37 μmol g-1h-1, which was 9 times and 1.2 times higher than the pure NH2-UIO-66 and CdS/NH2-UIO-66 powders.
Smart Images

Figure CN115999644B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of environmental and energy material synthesis, and specifically relates to a method for preparing a highly efficient electron transport MOF-based porous liquid photocatalyst, and research on the highly efficient photocatalytic reduction of carbon dioxide. Background Art
[0002] The development of industrialization will consume more and more fossil fuels, which brings about a large amount of carbon dioxide emissions, leading to serious global climate change. Nowadays, the public is paying more and more attention to the issue of carbon dioxide emissions, and various methods are being explored to convert carbon dioxide into other carbon-based chemicals to cope with the above threats. Among various CO2 conversion methods, photocatalytic CO2 reduction reaction has attracted widespread attention from researchers because it can use light energy to achieve CO2 reduction efficiently and cleanly.
[0003] Metal organic framework (MOF) is a new type of porous solid photocatalyst material. It has been increasingly used in the field of photocatalytic CO2 reduction due to its advantages of enhancing CO2 adsorption capacity and broadening spectral absorption range. In addition, MOF materials can be used as ideal carriers for the synthesis of various MOF-based composite materials. The suitable band gap between MOF and CdS is conducive to the formation of heterojunctions and can provide a strong driving force for the separation of photoexcited electron-hole pairs, thereby improving the photocatalytic activity. However, most photocatalytic CO2 reduction reactions are currently carried out in a liquid phase containing organic solvents.
[0004] However, since MOFs are usually non-dispersible in liquid phase, adjacent MOF nanoparticles are prone to aggregation under liquid phase conditions, and their poor stability in liquid phase limits their efficiency and stability in CO2 photoreduction in aqueous or organic phases. Therefore, it is highly desirable to develop synthetic protocols that facilitate the dispersibility of MOFs in liquid phase. To this end, we introduced MOF-based porous liquids to address these issues. MOF-based porous liquids are a new type of porous material with a permanent pore structure and a macroscopic liquid state. The simplest strategy is to disperse microporous materials such as MOFs and zeolites in solvents with larger molecular sizes. Due to the influence of external solvents, their dispersibility in liquid phase can be significantly improved. However, most of the large molecular size solvents wrapped outside the MOF particles cannot promote the photocatalytic reduction of CO2 because they do not have electron conduction ability.
[0005] Therefore, finding a large molecular size solvent that promotes electron transfer efficiency is crucial for constructing MOF-based porous liquid photocatalysts. Generally, good interfacial chemical bonding is the most common way to accelerate electron transfer efficiency. Studies have found that the surface acidic center -COOH can interact with the basic center -NH2 to form an amide bond. The amide bond provides an electron transfer channel to significantly improve interfacial charge transfer and separation.
[0006] In summary, how to promote the enrichment of electrons on MOFs in porous liquids based on interfacial bonding is of great significance for promoting the photocatalytic reduction of CO2. Summary of the invention
[0007] In order to overcome the deficiencies of the prior art, the present invention provides a highly efficient electron transport MOF-based porous liquid photocatalyst, using NH2-UIO-66 as a carrier and a large amount of CdS loaded on the surface to obtain CdS / NH2-UIO-66; through the compatibility principle of similar organic polymer structures and steric hindrance, the modified CdS / NH2-UIO-66 is combined with a large molecular size solvent ([M2070][IPA] ionic liquid) to form a new porous liquid (CdS / NH2-UIO-66 porous liquid). The carboxyl group on the isophthalic acid (IPA) in the ionic liquid can interact with the amino group on the surface of NH2-UIO-66 to form an amide bond. The formed amide bond can promote the enrichment of electrons on NH2-UIO-66, thereby attracting more photogenerated electrons on CdS to transfer to NH2-UIO-66, thereby achieving the purpose of improving the photocatalytic activity of the CdS / NH2-UIO-66 porous liquid.
[0008] The photocatalyst prepared by the present invention was used for the photocatalytic reduction of CO2, and the CO yield reached 71.37 μmol g -1 h -1 , which is nearly 9 times higher than that of pure NH2-UIO-66 and 1.2 times higher than that of the corresponding CdS / NH2-UIO-66 powder under the same reaction conditions.
[0009] In order to achieve the above technical objectives, the present invention provides the following solutions:
[0010] The present invention provides a method for preparing a highly efficient electron transport MOF-based porous liquid photocatalyst, which is carried out according to the following steps:
[0011] Step 1: Synthesis of NH2-UIO-66:
[0012] First, zirconium tetrachloride and 2-aminoterephthalic acid are dissolved in N,N-dimethylformamide; then, glacial acetic acid and hydrochloric acid are added respectively, and after ultrasonication, the obtained mixed solution is transferred to a polytetrafluoroethylene autoclave, and the autoclave is placed in an oven for hydrothermal reaction. After the reaction is completed, the product in the autoclave is collected by centrifugation, and is washed several times by centrifugation with N,N-dimethylformamide and acetone respectively, and finally the washed precipitated product is dried in vacuum to obtain NH2-UIO-66;
[0013] Step 2: Synthesis of CdS / NH2-UIO-66:
[0014] Dissolve cadmium acetate dihydrate in dimethyl sulfoxide to obtain a mixed solution, then add the NH2-UIO-66 obtained in step 1, transfer the mixed solution into a polytetrafluoroethylene-lined autoclave after ultrasonic treatment, and place the autoclave in an oven for hydrothermal reaction. After the reaction is completed, centrifuge the precipitate, wash it several times with acetone and ethanol respectively, and vacuum dry it to obtain CdS / NH2-UIO-66;
[0015] Step 3: Synthesis of macromolecular size solvent ([M2070][IPA] ionic liquid):
[0016] The polyetheramine M2070 is added to deionized water and methanol to dissolve, and then a certain amount of isophthalic acid (IPA) is added to obtain a mixed solution after dissolution, and then heated in an oil bath for evaporation, and the evaporated solution is vacuum dried to obtain a liquid product, namely, [M2070][IPA] ionic liquid;
[0017] Step 4: Synthesis of CdS / NH2-UIO-66 porous liquid photocatalyst:
[0018] The CdS / NH2-UIO-66 obtained in step 2 is dissolved in a mixture of deionized water and methanol, and then polyetheramine D2000 is added to obtain a mixed solution after dissolution, and the solvent is evaporated through an oil bath. After obtaining a solid, the evaporation is stopped. The obtained product is centrifugally washed several times with deionized water and anhydrous ethanol, respectively, and then vacuum dried to obtain D2000@CdS / NH2-UIO-66.
[0019] D2000@CdS / NH2-UIO-66 is then dispersed in toluene to obtain a solution referred to as solution A; [M2070][IPA] ionic liquid is then dispersed in toluene to obtain a solution referred to as solution B; then, solution B is slowly added to solution A; the solvent is then evaporated in an oil bath, and the evaporated solution is vacuum dried to obtain CdS / NH2-UIO-66 porous liquid, which is a MOF-based porous liquid photocatalyst.
[0020] Preferably, in step 1, the usage ratio of zirconium tetrachloride, 2-aminoterephthalic acid, N,N-dimethylformamide, glacial acetic acid and hydrochloric acid is 1 mmol: 1 mmol: 40-50 mL: 5 mL: 0.17 mL.
[0021] Preferably, in step 1, the reaction temperature of the hydrothermal reaction is 150° C. and the reaction time is 20 h;
[0022] Preferably, in step 1, the vacuum drying temperature is 120° C. and the time is 12 hours; the ultrasonic time is 30 minutes, and the number of cleanings is specifically 3-5 times.
[0023] Preferably, in step 2, the usage ratio of cadmium acetate dihydrate, NH2-UIO-66 and dimethyl sulfoxide is 0.0736 g:0.1 g:20 mL.
[0024] Preferably, in step 2, the reaction temperature of the hydrothermal reaction is 180° C. and the reaction time is 12 h;
[0025] Preferably, in step 2, the vacuum drying temperature is 120° C. and the time is 12 hours; the ultrasonic time is 30 minutes, and the number of cleanings is specifically 3-5 times.
[0026] Preferably, in step 3, the usage ratio of the polyetheramine M2070, deionized water, methanol and IPA is 1-5g:90mL:10mL:0.1-0.5g.
[0027] Preferably, in step 3, the oil bath temperature is 80° C., and the evaporation is stopped after the mixture is heated and evaporated to 1 / 10-1 / 8 of the mixture;
[0028] Preferably, in step 3, the vacuum drying temperature is 60° C. and the time is 24 hours.
[0029] Preferably, in step 4, the usage ratio of CdS / NH2-UIO-66, deionized water, methanol and polyetheramine D2000 is 0.1-0.5 g: 10 mL: 90 mL: 2-3 mL.
[0030] Preferably, in step 4, the first oil bath temperature is 80° C.; the first vacuum drying temperature is 60° C., and the time is 12 hours; and the number of cleanings is specifically 2-3 times.
[0031] Preferably, in step 4, the dosage ratio of the D2000@CdS / NH2-UIO-66 and toluene is 0.1-0.2 g:20 mL; the dosage ratio of the [M2070][IPA] ionic liquid and toluene is 0.1-0.2 g:20 mL; and the volume ratio of solution A and solution B when mixed is 1:1.
[0032] Preferably, in step 4, the second oil bath temperature is 80° C., and the evaporation is stopped after the mixture is heated and evaporated in the oil bath to 1 / 10-1 / 8 of the mixture; the second vacuum drying temperature is 60° C. and the time is 24 hours.
[0033] The MOF-based porous liquid photocatalyst prepared by the present invention is used for photocatalytic reduction of CO2.
[0034] Beneficial Effects
[0035] (1) The highly efficient electron transport MOF-based porous liquid photocatalyst prepared by the present invention forms an amide bond due to the interaction between the amino groups on the surface of NH2-UIO-66 and the carboxyl groups on the isophthalic acid in the [M2070][IPA] ionic liquid. The formed amide bond can promote the enrichment of electrons on NH2-UIO-66, thereby attracting more photogenerated electrons on CdS to transfer to NH2-UIO-66, thereby achieving the purpose of improving the performance of CdS / NH2-UIO-66 porous liquid photocatalytic reduction of CO2.
[0036] (2) The highly efficient electron transport MOF-based porous liquid photocatalyst prepared by the present invention has improved dispersibility in the liquid phase due to the existence of chemical bond affinity, thereby inhibiting the aggregation of NH2-UIO-66 particles and promoting its photocatalytic CO2 reduction under non-stirred liquid phase reaction conditions.
[0037] (3) The high-efficiency electron transport MOF-based porous liquid photocatalyst prepared by the present invention has the advantages of good processability and good operability in a flowing medium environment due to the good fluidity given by the external large molecular size solvent, which is conducive to industrial application. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 XRD spectra of CdS, fitted UIO-66, NH2-UIO-66, CdS / NH2-UIO-66 and CdS / NH2-UIO-66 porous liquids.
[0039] Figure 2 FT-IR spectra of different samples. Figure a shows NH2-UIO-66 and CdS / NH2-UIO-66; Figure b shows CdS / NH2-UIO-66 porous liquid and [M2070][IPA] ionic liquid.
[0040] Figure 3 SEM spectra (a, b, c and d) and EDX mapping spectra (e) of different samples, among which Figure a is NH2-UIO-66; Figure b is CdS / NH2-UIO-66; Figures c and d are CdS / NH2-UIO-66 porous liquid; Figure e is CdS / NH2-UIO-66 porous liquid.
[0041] Figure 4 Figure 1 is a diagram for investigating the fluidity of CdS / NH2-UIO-66 porous liquid; Figure a is a photograph of a drop of CdS / NH2-UIO-66 porous liquid taken with a toothpick; Figure b is a photograph of CdS / NH2-UIO-66 porous liquid; Figure c is a photograph of an inverted CdS / NH2-UIO-66 porous liquid after being placed at room temperature for 240 days.
[0042] Figure 5 This is an investigation diagram of the photoreduction of CO2 by NH2-UIO-66, CdS / NH2-UIO-66 and CdS / NH2-UIO-66 porous liquid.
[0043] Figure 6 This is the cycling experiment diagram of CdS / NH2-UIO-66 porous liquid.
[0044] Figure 7 Electron paramagnetic resonance spectra of NH2-UIO-66, CdS / NH2-UIO-66 and CdS / NH2-UIO-66 porous liquids. DETAILED DESCRIPTION
[0045] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0046] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0047] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0048] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention without departing from the scope or spirit of the present invention. Other embodiments obtained from the present invention description will be apparent to those skilled in the art.
[0049] A method for preparing a highly efficient electron transport MOF-based porous liquid photocatalyst is carried out according to the following steps:
[0050] Step 1: Synthesis of NH2-UIO-66:
[0051] First, zirconium tetrachloride and 2-aminoterephthalic acid are dissolved in N,N-dimethylformamide; then, glacial acetic acid and hydrochloric acid are added respectively, and after ultrasonication, the obtained mixed solution is transferred to a polytetrafluoroethylene autoclave, and the autoclave is placed in an oven for hydrothermal reaction. After the reaction is completed, the product in the autoclave is collected by centrifugation, and is washed several times by centrifugation with N,N-dimethylformamide and acetone respectively, and finally the washed precipitated product is dried in vacuum to obtain NH2-UIO-66;
[0052] The dosage ratio of zirconium tetrachloride, 2-aminoterephthalic acid, N,N-dimethylformamide, glacial acetic acid and hydrochloric acid is 1mmol: 1mmol: 40-50mL: 5mL: 0.17mL.
[0053] The reaction temperature of the hydrothermal reaction is 150°C and the reaction time is 20h;
[0054] The vacuum drying temperature is 120° C. and the time is 12 hours; the ultrasonic time is 30 minutes, and the cleaning times are specifically 3-5 times.
[0055] Step 2: Synthesis of CdS / NH2-UIO-66:
[0056] Dissolve cadmium acetate dihydrate in dimethyl sulfoxide to obtain a mixed solution, then add the NH2-UIO-66 obtained in step 1, transfer the mixed solution into a polytetrafluoroethylene-lined autoclave after ultrasonic treatment, and place the autoclave in an oven for hydrothermal reaction. After the reaction is completed, centrifuge the precipitate, wash it several times with acetone and ethanol respectively, and vacuum dry it to obtain CdS / NH2-UIO-66;
[0057] The usage ratio of the cadmium acetate dihydrate, NH2-UIO-66 and dimethyl sulfoxide is 0.0736 g: 0.1 g: 20 mL.
[0058] The reaction temperature of the hydrothermal reaction is 180°C and the reaction time is 12h;
[0059] The vacuum drying temperature is 120° C. and the time is 12 hours; the ultrasonic time is 30 minutes, and the cleaning times are specifically 3-5 times.
[0060] Step 3: Synthesis of macromolecular size solvent ([M2070][IPA] ionic liquid):
[0061] The polyetheramine M2070 is added to deionized water and methanol to dissolve, and then a certain amount of isophthalic acid (IPA) is added to obtain a mixed solution after dissolution, and then heated in an oil bath for evaporation, and the evaporated solution is vacuum dried to obtain a liquid product, namely, [M2070][IPA] ionic liquid;
[0062] The dosage ratio of the polyetheramine M2070, deionized water, methanol and IPA is 1-5g:90mL:10mL:0.1-0.5g.
[0063] The oil bath temperature is 80°C, and the evaporation is stopped after the mixture is heated and evaporated to 1 / 10-1 / 8 of the mixture;
[0064] The vacuum drying temperature is 60° C. and the time is 24 hours.
[0065] Step 4: Synthesis of CdS / NH2-UIO-66 porous liquid photocatalyst:
[0066] The CdS / NH2-UIO-66 obtained in step 2 is dissolved in a mixture of deionized water and methanol, and then polyetheramine D2000 is added to obtain a mixed solution after dissolution, and the solvent is evaporated through an oil bath. After obtaining a solid, the evaporation is stopped. The obtained product is centrifugally washed several times with deionized water and anhydrous ethanol, respectively, and then vacuum dried to obtain D2000@CdS / NH2-UIO-66.
[0067] D2000@CdS / NH2-UIO-66 is then dispersed in toluene to obtain a solution referred to as solution A; [M2070][IPA] ionic liquid is then dispersed in toluene to obtain a solution referred to as solution B; then, solution B is slowly added to solution A; the solvent is then evaporated in an oil bath, and the evaporated solution is vacuum dried to obtain CdS / NH2-UIO-66 porous liquid, which is a MOF-based porous liquid photocatalyst.
[0068] The dosage ratio of the CdS / NH2-UIO-66, deionized water, methanol and polyetheramine D2000 is 0.1-0.5 g: 10 mL: 90 mL: 2-3 mL.
[0069] The first oil bath temperature is 80°C; the first vacuum drying temperature is 60°C, and the time is 12 hours; the number of cleaning times is specifically 2-3 times.
[0070] The amount ratio of D2000@CdS / NH2-UIO-66 to toluene is 0.1-0.2 g:20 mL; the amount ratio of [M2070][IPA] ionic liquid to toluene is 0.1-0.2 g:20 mL; solution A and solution B are mixed.
[0071] The second oil bath temperature is 80°C, and the evaporation is stopped after the mixture is heated and evaporated to 1 / 10-1 / 8 of the mixture; the second vacuum drying temperature is 60°C and the time is 24 hours.
[0072] Evaluation of CO2 photocatalytic reduction activity:
[0073] 10 mg of photocatalyst was mixed in 30 mL of a solution containing 27 mL of acetonitrile and 3 mL of triethanolamine and then added to a 100 mL quartz glass reactor. Afterwards, the reaction apparatus was purged with pure CO2 gas (purity>99.999%) for 10 minutes, followed by more than two pressurized venting treatments to ensure that all impurities and trapped air were completely removed. Finally, the pressure was adjusted to 0.5 MPa. Before illumination, the reactor was installed below a light source system equipped with a 300-watt xenon lamp that simulated sunlight. The gaseous products were analyzed using a gas chromatograph (GC-2030) equipped with a thermal conductivity detector and a flame ionization detector. The carrier gas was Ar, the flow rate was 20 mL / min, and the column temperature was 333 K.
[0074] The present invention is further described below in conjunction with specific implementation examples. The present invention description and examples are only exemplary.
[0075] Embodiment 1:
[0076] (1) Synthesis of NH2-UIO-66:
[0077] First, 1mmol zirconium tetrachloride and 1mmol 2-aminoterephthalic acid were dissolved in 50mL N,N-dimethylformamide. Then, 5mL glacial acetic acid and 0.17mL hydrochloric acid were added as a regulator and a crystallizer, respectively. After half an hour of ultrasonication, the obtained mixed solution was transferred to a polytetrafluoroethylene autoclave, and the autoclave was placed in an oven and reacted at 150°C for 20 hours. After the reaction, the product in the autoclave was collected by centrifugation and washed 3 times with N,N-dimethylformamide and acetone respectively. Finally, the obtained product was dried at 120°C for 12 hours to obtain NH2-UIO-66.
[0078] (2) Synthesis of CdS / NH2-UIO-66:
[0079] First, 0.0736 g of cadmium acetate dihydrate was dissolved in 20 mL of dimethyl sulfoxide. Subsequently, 0.1 g of NH2-UIO-66 was added to the solution. After half an hour of ultrasonication, the mixture was transferred into a polytetrafluoroethylene-lined autoclave, and the autoclave was placed in an oven and reacted at 180°C for 12 hours. After the reaction, the mixed solution was centrifuged to obtain a precipitate, which was washed three times with acetone and ethanol respectively, and dried in a vacuum drying oven at 120°C for 12 hours to obtain CdS / NH2-UIO-66.
[0080] (3) Synthesis of Large Molecular Size Solvent ([M2070][IPA] Ionic Liquid)
[0081] 5 g of polyetheramine M2070 was added to a beaker, and 90 mL of deionized water and 10 mL of methanol were poured in to dissolve it. Then, 0.5 g of isophthalic acid (IPA) was slowly added to obtain a mixed solution after dissolution, and the solution was transferred to a three-necked flask, and then heated in an 80°C oil bath to evaporate to 1 / 10 of the mixed solution, and then the evaporation was stopped. The obtained solution was vacuum dried at 60°C for 24 hours to obtain [M2070][IPA] ionic liquid.
[0082] (4) Synthesis of CdS / NH2-UIO-66 porous liquid photocatalyst:
[0083] 0.3g CdS / NH2-UIO-66 was dissolved in a mixture of 10mL deionized water and 90mL methanol. After that, 3mL of polyetheramine D2000 was slowly added. After dissolution, the mixture was transferred to a three-necked flask and evaporated in an 80℃ oil bath. After obtaining a solid, evaporation was stopped. The obtained product was centrifugally washed twice with deionized water and anhydrous ethanol, respectively, and the precipitate was obtained and dried in a vacuum drying oven at 60℃ for 24 hours to obtain D2000@CdS / NH2-UIO-66.
[0084] After that, 0.2g of D2000@CdS / NH2-UIO-66 was first dispersed in 20mL of toluene. Then 0.2g of [M2070][IPA] ionic liquid was dispersed in 20mL of toluene. Next, the [M2070][IPA] ionic liquid mixture was slowly added to the D2000@CdS / NH2-UIO-66 suspension to obtain a mixed solution. The solvent was then evaporated in an 80°C oil bath until 1 / 10 of the mixed solution was reached and the evaporation was stopped. The resulting solution was dried in a 60°C vacuum drying oven for 24 hours to obtain a CdS / NH2-UIO-66 porous liquid, which was a MOF-based porous liquid photocatalyst.
[0085] Figure 1 XRD spectra of different samples, specifically XRD spectra of CdS, fitted UIO-66, NH2-UIO-66, CdS / NH2-UIO-66 and CdS / NH2-UIO-66 porous liquid;
[0086] It can be seen from the figure that all the diffraction peaks of the original NH2-UIO-66 can be well matched with the fitted UIO-66, indicating that NH2-UIO-66 has been successfully synthesized. The diffraction peaks of pure CdS at 26.1°, 44.0° and 51.9° can be attributed to the (111), (220) and (311) crystal planes, respectively. In addition, in the XRD spectrum of CdS / NH2-UIO-66, the main diffraction peaks of NH2-UIO-66 and CdS were detected, indicating that CdS has been successfully loaded on NH2-UIO-66. Moreover, the structure of NH2-UIO-66 did not change significantly after loading CdS, which means that the combination of NH2-UIO-66 and CdS will not affect its own structure. It is worth noting that for the XRD spectrum of CdS / NH2-UIO-66 porous liquid, the typical peaks of NH2-UIO-66 and CdS cannot be found. This is because NH2-UIO-66 is wrapped with too much ionic liquid.
[0087] Figure 2 FT-IR spectra of different samples, where a is NH2-UIO-66 and CdS / NH2-UIO-66; b is CdS / NH2-UIO-66 porous liquid and [M2070][IPA] ionic liquid;
[0088] It can be seen from the figure that the spectrum of CdS / NH2-UIO-66 shows vibration bands similar to those of NH2-UIO-66, which is because the peaks of inorganic CdS overlap with those of NH2-UIO-66;
[0089] In addition, in the spectra of CdS / NH2-UIO-66 porous liquid and [M2070][IPA] ionic liquid, -(CH2)- and CH bond peaks appeared, which were attributed to the polyetheramine M2070; this proves that CdS / NH2-UIO-66 is completely combined with [M2070][IPA] ionic liquid; compared with CdS / NH2-UIO-66 powder, CdS / NH2-UIO-66 porous liquid has a higher peak concentration at 3100-3400cm -1 The intensity of the broad absorption peak becomes weaker, indicating that the amount of amino groups decreases, which is attributed to the bonding of isophthalic acid in the ionic liquid with the amino groups on CdS / NH2-UIO-66 to form amide bonds.
[0090] It is worth noting that a -1 A new peak at was found in the CdS / NH2-UIO-66 porous liquid, which was attributed to the -NHCO- group, and further demonstrated that amide bonds were successfully formed in the CdS / NH2-UIO-66 porous liquid.
[0091] Figure 3SEM spectra and EDX mapping spectra of different samples, where a is NH2-UIO-66; b is CdS / NH2-UIO-66; c and d are CdS / NH2-UIO-66 porous liquid; e is CdS / NH2-UIO-66 porous liquid;
[0092] It can be seen from the figure that the original NH2-UIO-66 has the characteristics of regular octahedral shape with a diameter of about 100-300nm. At the same time, CdS / NH2-UIO-66 shows that CdS nanoparticles with an average particle size in the range of 5-20nm are uniformly distributed on the outer surface of NH2-UIO-66.
[0093] In addition, uniform, interconnected colloidal materials can be seen between CdS / NH2-UIO-66 particles, indicating that CdS / NH2-UIO-66 can be combined with [M2070][IPA] ionic liquid and maintain the original structure of NH2-UIO-66. Moreover, the EDX mapping images show the uniform distribution of C, S, Zr, Cd, N and O elements in the CdS / NH2-UIO-66 porous liquid.
[0094] Figure 4 This is an investigation on the fluidity of CdS / NH2-UIO-66 porous liquid. a is a photo of a drop of CdS / NH2-UIO-66 porous liquid dipped with a toothpick; b is a photo of CdS / NH2-UIO-66 porous liquid; c is a photo of CdS / NH2-UIO-66 porous liquid after being placed at room temperature for 240 days.
[0095] As can be seen from the figure: after a drop is dipped with a toothpick, the CdS / NH2-UIO-66 porous liquid drops rapidly within 2.0 seconds, proving its good fluidity. In addition, even after being placed for 240 days, the CdS / NH2-UIO-66 porous liquid still exhibits good fluidity, which also proves its uniform stability.
[0096] Figure 5 The graphs for the investigation of the photoreduction of CO2 by different samples, specifically the graphs for the investigation of the photoreduction of CO2 by NH2-UIO-66, CdS / NH2-UIO-66 and CdS / NH2-UIO-66 porous liquid;
[0097] As can be seen from the figure: NH2-UIO-66 exhibits poor photocatalytic performance with a CO production of 39.52 μmol / g. In contrast, CdS / NH2-UIO-66 has a CO production of 300.04 μmol / g, showing enhanced photocatalytic activity. The improved activity is related to the highly uniform dispersion of CdS nanoparticles on the surface of NH2-UIO-66.
[0098] It is noteworthy that by combining CdS / NH2-UIO-66 with [M2070][IPA] ionic liquid to form a porous liquid, the highest CO yield of CdS / NH2-UIO-66 porous liquid was 356.86 μmol / g, which is about 9 times that of NH2-UIO-66. The excellent performance observed on the CdS / NH2-UIO-66 porous liquid is attributed to the formed amide bond, which can promote the enrichment of electrons on NH2-UIO-66, thereby attracting more photogenerated electrons on CdS to transfer to NH2-UIO-66, thereby achieving the purpose of improving the photocatalytic activity of CdS / NH2-UIO-66 porous liquid.
[0099] Figure 6 This is the cycle experiment diagram of CdS / NH2-UIO-66 porous liquid;
[0100] It can be seen from the figure that the CdS / NH2-UIO-66 porous liquid has good stability and maintains a high photocatalytic performance during the three-cycle CO2 reduction process.
[0101] Figure 7 Electron paramagnetic resonance spectra of different samples, specifically, electron paramagnetic resonance spectra of NH2-UIO-66, CdS / NH2-UIO-66 and CdS / NH2-UIO-66 porous liquids.
[0102] As can be seen from the figure, when NH2-UIO-66 was irradiated by simulated sunlight, a Zr 3+ The corresponding weak EPR signal with a g value of 2.005 indicates that the electrons on the HOMO energy level associated with the organic ligand are excited to the LUMO energy level associated with Zr, converting the original Zr 4+ Transformed to Zr 3+ For CdS / NH2-UIO-66, a sharp and narrow EPR signal was observed at the same position, and a new peak appeared at g = 2.012, which is also attributed to Zr III This indicates that electrons are transferred from the CB of CdS to the LUMO of NH2-UIO-66, resulting in the formation of more Zr 3+ .
[0103] When the CdS / NH2-UIO-66 porous liquid is irradiated with simulated sunlight, it not only has the same EPR signals at g = 2.005 and 2.012, but also another new peak appears at g = 1.997, which is also attributed to Zr 3+ The EPR results show that the presence of amide bonds promotes the enrichment of electrons on NH2-UIO-66 in the CdS / NH2-UIO-66 porous liquid, thereby attracting more electrons to transfer from CdS to NH2-UIO-66.
[0104] Note: The above embodiments are only used to illustrate the present invention and are not intended to limit the technical solutions described in the present invention; therefore, although this specification has described the present invention in detail with reference to the above embodiments, a person skilled in the art should understand that the present invention can still be modified or replaced by equivalents; and all technical solutions and improvements thereof that do not depart from the spirit and scope of the present invention should be covered within the scope of the claims of the present invention.
Claims
1. A method for preparing a highly efficient electron transport MOF-based porous liquid photocatalyst, characterized in that: The following steps are involved: Step 1: Synthesis of NH2-UIO-66: First, zirconium tetrachloride and 2-aminoterephthalic acid are dissolved in N,N-dimethylformamide; then, glacial acetic acid and hydrochloric acid are added respectively, and after ultrasonication, the obtained mixed solution is transferred to a polytetrafluoroethylene autoclave, and the polytetrafluoroethylene autoclave is placed in an oven for hydrothermal reaction. After the reaction is completed, the product in the polytetrafluoroethylene autoclave is collected by centrifugation, and is washed several times by centrifugation with N,N-dimethylformamide and acetone respectively, and finally the washed precipitated product is dried by vacuum drying to obtain NH2-UIO-66; Step 2: Synthesis of CdS / NH2-UIO-66: Dissolve cadmium acetate dihydrate in dimethyl sulfoxide to obtain a mixed solution, then add NH2-UIO-66 obtained in step 1, transfer the mixed solution into a polytetrafluoroethylene-lined autoclave after ultrasonic treatment, and place the polytetrafluoroethylene-lined autoclave in an oven for hydrothermal reaction. After the reaction is completed, centrifuge the precipitate, wash it several times with acetone and ethanol respectively, and vacuum dry it to obtain CdS / NH2-UIO-66; Step 3: Synthesis of macromolecular size solvent ([M2070][IPA] ionic liquid): The polyetheramine M2070 is added to deionized water and methanol to dissolve, and then a certain amount of isophthalic acid is added to obtain a mixed solution after dissolution, and then heated in an oil bath for evaporation, and the evaporated solution is vacuum dried to obtain a liquid product, namely [M2070][IPA] ionic liquid; Step 4: Synthesis of CdS / NH2-UIO-66 porous liquid photocatalyst: S1, dissolving the CdS / NH2-UIO-66 obtained in step 2 in a mixture of deionized water and methanol, then adding polyetheramine D2000 to obtain a mixed solution after dissolution, and evaporating the solvent through an oil bath to stop evaporation after obtaining a solid, and washing the obtained product by centrifugation with deionized water and anhydrous ethanol for several times, and then vacuum drying to obtain D2000@CdS / NH2-UIO-66; S2, D2000@CdS / NH2-UIO-66 was dispersed in toluene to obtain a solution, which was recorded as solution A; Then, the [M2070][IPA] ionic liquid is dispersed in toluene to obtain a solution recorded as solution B; then, solution B is slowly added into solution A; then, the solvent is evaporated through an oil bath, and the evaporated solution is vacuum dried to obtain CdS / NH2-UIO-66 porous liquid photocatalyst, which is a MOF-based porous liquid photocatalyst.
2. The method for preparing a highly efficient electron transport MOF-based porous liquid photocatalyst according to claim 1, characterized in that: In step 1, the amount ratio of zirconium tetrachloride, 2-aminoterephthalic acid, N,N-dimethylformamide, glacial acetic acid and hydrochloric acid is 1 mmol: 1 mmol: 40-50 mL: 5 mL: 0.17 mL.
3. The method for preparing a highly efficient electron transport MOF-based porous liquid photocatalyst according to claim 1, characterized in that: In step 1, the reaction temperature of the hydrothermal reaction is 150° C., and the reaction time is 20 h; the temperature of the vacuum drying is 120° C., and the time is 12 hours; the time of the ultrasonication is 30 min, and the number of cleanings is specifically 3-5 times.
4. The method for preparing a highly efficient electron transport MOF-based porous liquid photocatalyst according to claim 1, characterized in that: In step 2, the usage ratio of cadmium acetate dihydrate, NH2-UIO-66 and dimethyl sulfoxide is 0.0736 g: 0.1 g: 20 mL.
5. The method for preparing a highly efficient electron transport MOF-based porous liquid photocatalyst according to claim 1, characterized in that: In step 2, the reaction temperature of the hydrothermal reaction is 180° C., and the reaction time is 12 h; the temperature of the vacuum drying is 120° C., and the time is 12 hours; the time of the ultrasonication is 30 min, and the number of cleanings is specifically 3-5 times.
6. The method for preparing a highly efficient electron transport MOF-based porous liquid photocatalyst according to claim 1, characterized in that: In step 3, the usage ratio of the polyetheramine M2070, deionized water, methanol and isophthalic acid is 1-5 g: 90 mL: 10 mL: 0.1-0.5 g.
7. The method for preparing a highly efficient electron transport MOF-based porous liquid photocatalyst according to claim 1, characterized in that: In step 3, the oil bath temperature is 80° C., and the mixture is heated and evaporated in the oil bath until 1 / 10-1 / 8 of the mixture is evaporated, and then the evaporation is stopped; the vacuum drying temperature is 60° C. and the time is 24 hours.
8. The method for preparing a highly efficient electron transport MOF-based porous liquid photocatalyst according to claim 1, characterized in that: In S1 of step 4, the dosage ratio of CdS / NH2-UIO-66, deionized water, methanol and polyetheramine D2000 is 0.1~0.5 g:10 mL:90 mL:2~3 mL; the temperature of the oil bath is 80°C; the temperature of the vacuum drying is 60°C, and the time is 12 hours; and the washing number is specifically 2-3 times.
9. The method for preparing a highly efficient electron transport MOF-based porous liquid photocatalyst according to claim 1, characterized in that: In S2 of step 4, the amount ratio of D2000@CdS / NH2-UIO-66 and toluene is 0.1~0.2 g:20mL; the amount ratio of [M2070][IPA] ionic liquid and toluene is 0.1~0.2 g:20mL; the volume ratio of solution A and solution B when mixed is 1:1; the temperature of the oil bath is 80°C, and the evaporation is stopped after heating and evaporating in the oil bath pot to 1 / 10-1 / 8 of the mixed solution; the temperature of vacuum drying is 60°C and the time is 24 hours.
10. Use of the MOF-based porous liquid photocatalyst prepared according to the method according to any one of claims 1 to 9 in photocatalytic reduction of CO2.
Citation Information
Patent Citations
Catalyst for photo-catalytically decomposing water to produce hydrogen and preparation method of catalyst
CN103316714A
Preparation method for metal organic framework material UIO-66 (NH2) / rodlike cadmium sulfide composite photocatalyst
CN107670696A